2004
DOI: 10.1556/avet.52.2004.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inorganic and organic manganese supplementation on the performance and tissue manganese content of broiler chicks

Abstract: The effects of dietary levels of manganese (Mn) in inorganic (MnO) and organic (Mn fumarate) forms were evaluated on cockerel chicks. A basal cornsoybean diet with 23 mg/kg Mn was supplemented with levels of 0, 30, 60 and 240 ppm Mn from both Mn sources. Each treatment was replicated in five pens of 10 chicks. The chicks were fed diets ad libitum from 14 to 49 days of age, after which five birds per treatment were sacrificed for pathomorphological examinations and analysis. The treatments did not exert signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 9 publications
3
17
0
1
Order By: Relevance
“…The accumulation of trace minerals (Zn and Mn) in tibia has been accepted by several researchers as an indicator of their bioavailability [7,18,19]. In the current study, as expected, the retention of Zn and Mn in tibia was directly related to their levels of inclusion in the diets, which was in conformity with the findings of Huang et al [7] and Sunder et al [20].…”
Section: Tibia Weight Percent Tibia Ash and Trace Mineral Retentionsupporting
confidence: 91%
See 2 more Smart Citations
“…The accumulation of trace minerals (Zn and Mn) in tibia has been accepted by several researchers as an indicator of their bioavailability [7,18,19]. In the current study, as expected, the retention of Zn and Mn in tibia was directly related to their levels of inclusion in the diets, which was in conformity with the findings of Huang et al [7] and Sunder et al [20].…”
Section: Tibia Weight Percent Tibia Ash and Trace Mineral Retentionsupporting
confidence: 91%
“…Perhaps the same analogy was applicable in our study with higher levels of Zn and Mn, which depressed Cu accumulation in liver. We also observed that the relative uptake of Zn and Mn by tibia was higher than liver tissue, indicating that the tibia was more responsive to mineral accumulation than liver [19]. This could be the possible reason for lower mineral concentration in liver compared to bone tissue.…”
Section: Trace Mineral Retention In Liver Tissuementioning
confidence: 60%
See 1 more Smart Citation
“…This may be attributed to the fact that Mn‐S is more easily released manganese ions that interact with other dietary components and organic manganese are generally less sensitive to the inhibitory action of other compounds and preventing its conversion into insoluble chemical compounds in the intestine. Berta, Andrásofszky, Bersenyi, Glavits, Gaspardy and Fekete () also found that when broiler chicks fed diets supplemented with manganese at 7 weeks, the body weight of birds fed the inorganic manganese was lower than that of the birds fed the organic manganese, even in cases where dietary Mn from inorganic manganese was far higher than organic manganese. Juvenile cobia fed higher dietary Mn levels more than the requirement did not significantly reduce the growth performance, indicating that fish can be tolerated to a greater extent on manganese toxicity.…”
Section: Discussionmentioning
confidence: 94%
“…Berta et al . () found that when broiler chicks fed diets supplemented with manganese at levels of 240 mg Mn kg −1 , the Mn concentrations in kidney and tibial of broiler chicks fed inorganic manganese were higher than organic manganese, whereas the opposite in liver was observed. Li et al .…”
Section: Discussionmentioning
confidence: 99%